A MOF-derived carbon nanotube / carbon matrix composite material and its preparation method and application
By preparing MOF-derived carbon nanotubes in situ on the carbon matrix, the problems of low cycling performance and low catalytic performance of traditional electrodes are solved, and MOF-derived carbon nanotube/carbon matrix composites with high cycling stability and excellent catalytic performance are achieved.
Patent Information
- Application Number
- CN202211721242.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The electrodes where traditional carbon nanotube powders adhere to carbon cloth or carbon felt have problems with low cycling performance and low catalytic performance.
Using MOF-derived carbon nanotube/carbon matrix composite material, the carbon matrix, cobalt salt solution and dimethylimidazole solution are mixed to form MOF materials, and carbonization and recombination are carried out in high C and high N atmospheres to prepare Co-containing MOF-derived carbon nanotubes of metal sites and N atoms.
The cyclic stability and catalytic performance of the electrode material are improved, and the uranyl removal efficiency of more than 97% can be maintained after 30 consecutive cycles, and the hydrogen production efficiency has no significant attenuation after 10 cycles during the decomposition of the aquatic hydrogen production process.
Smart Images

Figure CN115945208B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a MOF-derived carbon nanotube / carbon matrix composite material and a preparation method and application thereof. Background Art
[0002] For the sustainable development of environmental energy, it is crucial to develop renewable clean energy technology. Among them, (photo) electrochemical energy technology has certain advantages in dealing with environmental and energy issues, such as: treating organic matter in water, decomposing water energy, oxidizing ammonia nitrogen, fixing carbon dioxide, fuel cells and supercapacitors.
[0003] In traditional (photo) electrochemical energy technology, noble metals are often used as catalysts. Due to the high cost of traditional noble metal catalysts, electrodes formed by bonding carbon nanotube powders with carbon cloth or carbon felt are often used as substitutes. However, electrodes formed by bonding carbon nanotube powders with carbon cloth or carbon felt have problems of low cycle performance and low catalytic performance. Summary of the invention
[0004] The object of the present invention is to provide a MOF-derived carbon nanotube / carbon matrix composite material and a preparation method and application thereof. The electrode material of the present invention has excellent cycle stability and catalytic performance.
[0005] The present invention provides a method for preparing a MOF-derived carbon nanotube / carbon matrix composite material, comprising the following steps:
[0006] The carbon matrix, the cobalt salt solution and the dimethyl imidazole solution are mixed to generate a coordination reaction, thereby forming a MOF material on the surface of the carbon matrix to obtain a MOF-modified carbon matrix;
[0007] Decomposing a carbon source containing N in an inert atmosphere to form a high-C and high-N atmosphere;
[0008] Carbonizing and reorganizing the MOF-modified carbon matrix in the high-C and high-N atmosphere to obtain a MOF-derived carbon nanotube / carbon matrix composite material;
[0009] The temperature of the carbonization and recombination is 600-800° C., and the time is 1-6 hours.
[0010] Preferably, the decomposition reaction temperature is 400-500° C. and the time is 1-4 hours.
[0011] Preferably, the MOF loading in the MOF-modified carbon matrix is 0.3-0.5 mg / cm 2 .
[0012] Preferably, the cobalt salt solution includes cobalt sulfate solution or cobalt nitrate solution.
[0013] Preferably, the molar ratio of the cobalt salt in the cobalt salt solution to the dimethylimidazole in the dimethylimidazole solution is 1:4-10.
[0014] Preferably, the mass ratio of the MOF-modified carbon matrix to the N-containing carbon source is 1:0.4-1.
[0015] Preferably, the N-containing carbon source includes one or more of urea, dicyandiamide and melamine.
[0016] Preferably, the heating rate to the decomposition reaction temperature and the heating rate to the carbonization and recombination temperature are independently no higher than 10°C / min.
[0017] The present invention also provides a MOF-derived carbon nanotube / carbon matrix composite material prepared by the preparation method described in the above scheme, comprising a carbon matrix and MOF-derived carbon nanotubes loaded on the carbon matrix; the MOF-derived carbon nanotubes contain elements C, N, O and Co, and have a tube diameter of 10 to 250 nm.
[0018] The present invention also provides the use of the MOF-derived carbon nanotube / carbon matrix composite material described in the above scheme as an electrode material in a photoelectrocatalytic system or an electrocatalytic system.
[0019] The invention provides a method for preparing a MOF-derived carbon nanotube / carbon matrix composite material, comprising the following steps: mixing a carbon matrix, a cobalt salt solution and a dimethyl imidazole solution to generate a coordination reaction, forming a MOF material on the surface of the carbon matrix, and obtaining a MOF-modified carbon matrix; performing a decomposition reaction on a carbon source containing N in an inert atmosphere to form an atmosphere of high C and high N; carbonizing and reorganizing the MOF-modified carbon matrix in the atmosphere of high C and high N to obtain a MOF-derived carbon nanotube / carbon matrix composite material; the temperature of the carbonization and reorganization is 600-800° C., and the time is 1-6 hours. The present invention uses MOF as a raw material, treats MOF in a high C and high N atmosphere, promotes MOF to be carbonized and reorganized into carbon nanotubes, and simultaneously incorporates N elements, so that the prepared MOF-derived carbon nanotubes have Co metal sites (provided by MOF) and N atoms, and have a pore structure, thereby increasing the active sites of the carbon nanotubes and improving the catalytic performance of the carbon nanotubes; and the present invention prepares carbon nanotubes in situ on a carbon matrix, thereby increasing the binding force between the carbon nanotubes and the carbon matrix, making it difficult for the carbon nanotubes and the carbon matrix to be peeled off during the catalytic process, thereby improving the cycle stability. In addition, the present invention also controls the temperature and time of carbonization and reorganization, so that the electrode material has better catalytic activity and excellent cycle stability.
[0020] The results of the embodiment show that when the MOF-derived carbon nanotube / carbon matrix composite material of the present invention is used as an electrode material to catalyze the degradation of uranyl ions in water, the removal efficiency of uranyl ions reaches 100%, and after 30 consecutive cycles, the removal efficiency of uranyl ions reaches more than 97%; when the electrode material of the present invention is used to decompose water to produce hydrogen, the hydrogen production rate is 45 μmol·cm -2 ·h -1 In the process of cyclic test of decomposing water to produce hydrogen, the hydrogen production efficiency did not decay significantly after 10 cycles, and had good stability performance; the supercapacitor made of the electrode material of the present invention can be 2 Provides 601.9F·g -1 The specific capacitance at 5 mA / cm 2 After 3000 charge and discharge cycles, 84% of the capacity was retained, showing excellent cycle stability.
[0021] Furthermore, the electrode material of the present invention has good electrical conductivity and good electron transfer capability when used as the cathode in a hybrid series photocatalytic fuel cell; the electrode material of the present invention has good hydrophilicity and good adsorption performance, and has good stability and a long service life in catalyzing the degradation of antibiotics in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the preparation process of the MOF-derived carbon nanotube / carbon matrix composite material of the present invention;
[0023] Figure 2 This is the XRD pattern of the MOF-derived carbon nanotube / carbon matrix composite material of Example 1;
[0024] Figure 3 This is a SEM image of the MOF-modified carbon substrate of Example 1 at a magnification of 10 μm;
[0025] Figure 4 This is a SEM image of the MOF-modified carbon substrate of Example 1 at a magnification of 1 μm;
[0026] Figure 5 This is a SEM image of the MOF-derived carbon nanotube / carbon matrix composite material of Example 1 at a magnification of 10 μm;
[0027] Figure 6 This is a SEM image of the MOF-derived carbon nanotube / carbon matrix composite material of Example 1 at a magnification of 1 μm;
[0028] Figure 7 TEM image of the MOF-derived carbon nanotube / carbon matrix composite material of Example 1;
[0029] Figure 8This is the XPS spectrum of the MOF-derived carbon nanotube / carbon matrix composite material of Example 1;
[0030] Fig. 9 This is a graph showing the test results of uranium removal efficiency in Application Example 1;
[0031] Fig.10 This is a graph showing the uranium removal efficiency cycle test results of Application Example 1;
[0032] Fig.11 The cyclic voltammetry curve of comparative application example 1 is shown;
[0033] Fig.12 The impedance test results of the three-electrode system of Application Example 3 and Comparative Application Example 2 are shown. DETAILED DESCRIPTION
[0034] The present invention provides a method for preparing a MOF-derived carbon nanotube / carbon matrix composite material, which is characterized by comprising the following steps:
[0035] The carbon matrix, the cobalt salt solution and the dimethylimidazole solution are mixed to generate a coordination reaction, thereby forming a MOF material on the surface of the carbon matrix to obtain a MOF-modified carbon matrix;
[0036] Decomposing a carbon source containing N in an inert atmosphere to form a high-C and high-N atmosphere;
[0037] Carbonizing and reorganizing the MOF-modified carbon matrix in the high-C and high-N atmosphere to obtain a MOF-derived carbon nanotube / carbon matrix composite material;
[0038] The temperature of the carbonization and recombination is 600-800° C., and the time is 1-6 hours.
[0039] The present invention mixes a carbon matrix, a cobalt salt solution and a dimethyl imidazole solution to generate a coordination reaction, thereby forming an MOF material on the surface of the carbon matrix to obtain a MOF-modified carbon matrix.
[0040] In the present invention, the mixing preferably comprises immersing the carbon substrate in a cobalt salt solution and then adding a dimethylimidazole solution to the resulting mixture.
[0041] In the present invention, the carbon matrix preferably includes carbon felt, and the carbon felt is preferably commercial carbon felt. When the carbon matrix is carbon felt, the present invention preferably performs a first cleaning, an acidification treatment, and a second cleaning on the carbon felt in sequence before mixing the carbon matrix, the cobalt salt solution, and the dimethyl imidazole solution. The present invention has no special limitation on the size of the carbon felt, and any size is acceptable. Specifically, in the embodiment of the present invention, it is 2×5 cm. The present invention has no special limitation on the first cleaning, and the impurities on the surface of the carbon felt can be washed away by a method well known to those skilled in the art. In the present invention, the acidification treatment preferably includes placing the carbon felt after the first cleaning in a strong acid aqueous solution; the mass ratio of the carbon felt to the strong acid aqueous solution is preferably 1:5. The mass concentration of the strong acid aqueous solution is preferably 20-50%, and the strong acid aqueous solution is preferably a nitric acid solution. The nitric acid solution has a stronger oxidizing property, and can oxidize and remove the functional groups and impurities on the surface of the carbon felt, so that the growth distribution of MOF-derived carbon nanotubes is more uniform. In the present invention, the temperature of the acidification treatment is preferably 70°C, and the time is preferably 1-20h. The carbon felt after acidification has a higher carbonization degree and better hydrophilicity, making the growth distribution of MOF-derived carbon nanotubes more uniform. The present invention has no special limitation on the cleaning agent for the second cleaning, and it only needs to clean the unreacted strong acid solution. Specifically, in the embodiment of the present invention, it is deionized water.
[0042] In the present invention, the cobalt salt solution preferably includes a cobalt sulfate solution or a cobalt nitrate solution; the molar ratio of the cobalt salt in the cobalt salt solution to the dimethylimidazole in the dimethylimidazole solution is preferably 1:4 to 10, more preferably 1:5 to 8, and further preferably 1:6 to 7. In the present invention, the concentration of the dimethylimidazole solution is preferably 0.4M.
[0043] In the present invention, the temperature of the coordination reaction is preferably room temperature. The present invention has no special limitation on the time of the coordination reaction, as long as the loading of MOF in the MOF-modified carbon matrix is 0.3-0.5 mg / cm 2 Specifically, the coordination reaction time in the embodiment of the present invention is 3 hours. During the coordination reaction, the cobalt salt and dimethylimidazole undergo coordination reaction to generate MOF.
[0044] After the coordination reaction is completed, the present invention preferably rinses the obtained coordination reaction product with ethanol and water and dries it to obtain the MOF modified carbon matrix. The present invention has no special limitation on the ethanol and water rinsing, and the unreacted raw materials can be removed cleanly using a scheme well known to those skilled in the art. The present invention has no special limitation on the drying, and the drying can be performed using a scheme well known to those skilled in the art.
[0045] The present invention decomposes a carbon source containing N in an inert atmosphere to form an atmosphere high in C and N. In the present invention, the carbon source containing N includes one or more of urea, dicyandiamide and melamine.
[0046] In the present invention, the temperature of the decomposition reaction is preferably 400-500°C, more preferably 450-480°C; the time is preferably 1-4h, more preferably 2-3h. The heating rate to the decomposition reaction temperature is preferably not higher than 10°C / min, more preferably 2-8°C / min, and further preferably 4-6°C / min. In the present invention, the gas in the inert atmosphere is preferably argon.
[0047] After forming a high C and high N atmosphere, the present invention carbonizes and reorganizes the MOF-modified carbon matrix in the high C and high N atmosphere to obtain a MOF-derived carbon nanotube / carbon matrix composite material. In the present invention, the mass ratio of the MOF-modified carbon matrix to the carbon source containing N is preferably 1:0.4-1, more preferably 1:0.5-0.8, and further preferably 1:0.6-0.7. The relative excess of carbon source is conducive to the carbonization and reorganization of organic ligands in MOF into carbon nanotubes under a high concentration of C source. In the present invention, the temperature of the carbonization and reorganization is 600-800°C, preferably 700-750°C; the time is 1-6h, more preferably 3-5h. During the carbonization and reorganization process, the organic ligands in MOF are carbonized and curled to form nanotubes (i.e., reorganized), and react with N in the atmosphere to obtain MOF-derived carbon nanotubes containing N and Co.
[0048] In the present invention, the heating rate to the carbonization and recombination temperature is preferably not higher than 10°C / min, more preferably 2-8°C / min, and further preferably 4-6°C / min.
[0049] In the present invention, the decomposition reaction, carbonization and recombination are preferably carried out in a tube furnace. When the decomposition reaction, carbonization and recombination are carried out in a tube furnace, Figure 1 As shown, the present invention preferably places the MOF-modified carbon matrix and the N-containing carbon source into a tubular furnace in an inert atmosphere; the N-containing carbon source is at the front end of the tubular furnace; the MOF-modified carbon matrix is at the rear end of the tubular furnace, and the temperature of the tubular furnace is sequentially increased to the temperature of decomposition reaction, carbonization and recombination.
[0050] After carbonization and recombination, the present invention also preferably cools the obtained carbonization and recombination products naturally to obtain the electrode material.
[0051] The present invention uses MOF as a raw material, treats MOF in a high C and high N atmosphere, promotes MOF to be carbonized and reorganized into carbon nanotubes, and simultaneously incorporates N elements, so that the prepared MOF-derived carbon nanotubes have Co metal sites (provided by MOF) and N atoms, and have a pore structure, which increases the active sites of the carbon nanotubes and improves the catalytic performance of the carbon nanotubes; and the present invention prepares carbon nanotubes in situ on carbon felt, improves the binding force between the carbon nanotubes and the carbon felt, makes it difficult for the carbon nanotubes and the carbon felt to be peeled off during the catalytic process, and improves the cycle stability. In addition, the present invention also controls the temperature and time of carbonization and reorganization, so that the electrode material has better catalytic activity and excellent cycle stability.
[0052] The present invention also provides a MOF-derived carbon nanotube / carbon matrix composite material prepared by the preparation method described in the above scheme, comprising a carbon matrix and MOF-derived carbon nanotubes loaded on the carbon matrix; the MOF-derived carbon nanotubes contain elements C, N, O and Co, and have a tube diameter of 10 to 250 nm.
[0053] The composite material of the present invention has good electrical conductivity and good electron transfer capability when used as the cathode in a hybrid series photocatalytic fuel cell; the composite material of the present invention has good hydrophilicity and good adsorption performance, and has good stability and a long service life in catalytic degradation of antibiotics in water. The carbon felt substrate and the carbon nanotube structure ensure that the material has excellent electrical conductivity; a large number of N and O-containing groups introduced during the formation of the carbon nanotubes give it excellent adsorption performance and hydrophilicity.
[0054] The present invention also provides the use of the MOF-derived carbon nanotube / carbon matrix composite material prepared by the preparation method described in the above scheme or the MOF-derived carbon nanotube / carbon matrix composite material described in the above scheme as an electrode material in a photoelectrocatalytic system or an electrocatalytic system. The application is preferably one of removing heavy metal ions in water, removing antibiotics in water, decomposing water to produce hydrogen, oxidizing ammonia nitrogen, reducing nitrate nitrogen, reducing oxygen, producing hydrogen peroxide, sensors and ion battery materials. The heavy metal ions are preferably uranyl ions.
[0055] When the electrode material is used to remove uranyl ions, the method of application preferably comprises the following steps:
[0056] The composite photoanode and the electrode material are placed in wastewater containing uranyl ions, and the electrode material is connected to a mixed series photocatalytic fuel cell through an external circuit to remove the uranyl ions.
[0057] The present invention has no particular limitation on the components of the wastewater containing uranyl ions, and any components well known to those skilled in the art may be used.
[0058] When the electrode material is used to decompose water to produce hydrogen, the application method preferably includes the following steps:
[0059] After placing the composite photoanode and the electrode material in an electrolyte solution, the electrode material is connected to a hybrid series photocatalytic fuel cell through an external circuit to decompose water to produce hydrogen. When used to decompose water to produce hydrogen, the electrolyte solution preferably includes a non-oxidative reduction inorganic salt solution; the concentration of the electrolyte is preferably 0.01 to 5 mol / L; the non-oxidative reduction inorganic salt solution preferably includes one of a Na2SO4 solution, a K2SO4 solution and a phosphate buffer solution. .
[0060] In the present invention, when used to remove uranyl ions or decompose water to produce hydrogen, the composite photoanode is preferably a superposition of a semiconductor material film and a commercial silicon cell; the semiconductor material film preferably includes one of a titanium dioxide film, a tungsten trioxide film, a bismuth vanadate film and a bismuth vanadate / tungsten trioxide heterojunction film.
[0061] In the present invention, the light source used in the hybrid series photocatalytic fuel cell is preferably simulated sunlight or real sunlight.
[0062] In the photoelectrocatalytic system, the composite photoanode generates photogenerated charges, and the partial light that passes through the composite photoanode, which is a semiconductor material thin film, excites the photovoltaic cell to generate voltage to efficiently drive the photogenerated electrons to migrate to the cathode through an external circuit, and redox reactions occur on the surface of the thin film electrode and the cathode respectively, and a loop is formed through the external circuit, thereby realizing self-driven photoelectrocatalytic decomposition of water to produce hydrogen and self-driven photocatalytic removal of uranyl ions in water.
[0063] To further illustrate the present invention, the MOF-derived carbon nanotube / carbon matrix composite material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0064] Example 1
[0065] (1) The commercial carbon felt was cleaned by a known method and then placed in a nitric acid solution with a mass concentration of 40% at a temperature of 70° C. for acidification for 1 h (the mass ratio of the carbon felt to the nitric acid solution was 1:5), and then rinsed with a large amount of deionized water;
[0066] (2) The carbon felt treated in step (1) was placed in 0.04M cobalt nitrate, and a 0.4M dimethylimidazole solution was poured into the resulting mixture. After 3 hours of growth at room temperature, the carbon felt was taken out, rinsed with ethanol and water, and dried to obtain a MOF loading of 0.3 mg / cm 2 MOF modified carbon matrix.
[0067] (3) 5 g of the MOF-modified carbon matrix obtained in step (2) was placed in a tubular furnace, and 3 g of melamine was added to the front end. The temperature was increased from room temperature to 400°C at a heating rate of 10°C / min under an argon atmosphere for 2 h, and then increased to 700°C at a heating rate of 5°C / min for 2 h. After natural cooling, a MOF-derived carbon nanotube / carbon matrix composite material was obtained with a tube diameter of 150 to 250 nm.
[0068] The original carbon felt (denoted as CF) and the MOF-derived carbon nanotube / carbon matrix composite material (denoted as CG-700) prepared in Example 1 were subjected to XRD analysis. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the diffraction peaks at 25.8° of the original carbon felt and the MOF-derived carbon nanotube / carbon matrix composite material of this embodiment are similar to the crystal plane (002) of graphite carbon. Compared with the original carbon felt, the diffraction peaks at 44.2° and 51.3° of the MOF-derived carbon nanotube / carbon matrix composite material of this embodiment correspond to the (111) and (200) crystal planes of the Co metal element, respectively.
[0069] The MOF-modified carbon matrix prepared in Example 1 was subjected to SEM analysis at different magnifications. The results are as follows: Figure 3 and Figure 4 As shown. Figure 3 It can be seen that MOF materials are evenly distributed on carbon fiber fibers; Figure 4 It can be seen that MOF material is a nanosheet array structure.
[0070] The MOF-derived carbon nanotube / carbon matrix composite material prepared in Example 1 was subjected to SEM analysis at different magnifications. The results are as follows: Figure 5 and Figure 6 As shown. Figure 5 It can be seen that the carbon felt fiber filaments grow into nanotube structures. Figure 6 It can be seen that the nanotubes are arranged in a random structure.
[0071] The MOF-derived carbon nanotube / carbon matrix composite material prepared in Example 1 was subjected to TEM analysis. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that in the MOF-derived carbon nanotube / carbon matrix composite material prepared in Example 1, a plurality of Co nanoparticles are loaded on the wall of a single nanotube.
[0072] The MOF-derived carbon nanotube / carbon matrix composite material prepared in Example 1 was subjected to XPS analysis, and the results were as follows: Figure 8 As shown. Figure 8 It can be seen that the surface of the electrode material of this embodiment mainly contains C, N, O, and Co elements.
[0073] Example 2
[0074] (1) After cleaning the commercial carbon felt by a known method, the carbon felt was placed in a nitric acid solution with a mass concentration of 20% at 70° C. for acidification for 1 h (the mass ratio of the carbon felt to the nitric acid solution was 1:5), and then rinsed with a large amount of deionized water;
[0075] (2) The carbon felt treated in step (1) was placed in a 0.04M cobalt nitrate solution, and a 0.4M dimethylimidazole solution was poured into the resulting mixture. After the growth time at room temperature was greater than 3 hours, the carbon felt was taken out, rinsed with ethanol and water, and dried to obtain a MOF loading of 0.3 mg / cm 2 MOF modified carbon matrix.
[0076] (3) After rinsing and drying 5 g of the MOF-modified carbon matrix obtained in step (2), the mixture was placed in a tubular furnace, and 5 g of urea was added to the front end. The mixture was heated from room temperature to 400 °C at a heating rate of 10 °C / min for 4 h in an argon atmosphere, and then heated to 600 °C at a heating rate of 5 °C / min for 6 h. After natural cooling, a MOF-derived carbon nanotube / carbon matrix composite material was obtained, with a tube diameter of 100 to 200 nm.
[0077] The MOF-derived carbon nanotube / carbon matrix composite material (denoted as CG-600) prepared in Example 2 was subjected to XRD analysis, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the original carbon felt and the MOF-derived carbon nanotube / carbon matrix composite material of this embodiment have similar diffraction peaks at 25.8°, which is the crystal plane (002) of graphite carbon, but the diffraction peaks of the (111) and (200) crystal planes of the Co metal element at 44.2° and 51.3° are smaller.
[0078] Example 3
[0079] (1) After cleaning the commercial carbon felt by a known method, the carbon felt was placed in a 30% nitric acid solution at 70° C. for acidification for 1 h (the mass ratio of the carbon felt to the nitric acid solution was 1:5), and then rinsed with a large amount of deionized water;
[0080] (2) The carbon felt treated in step (1) was placed in a 0.04M cobalt nitrate solution, and a 0.4M dimethylimidazole solution was poured into the resulting mixture. After the growth time at room temperature was greater than 3 hours, the carbon felt was taken out, rinsed with ethanol and water, and dried to obtain a MOF loading of 0.3 mg / cm 2 MOF modified carbon matrix.
[0081] (3) 5 g of the MOF-modified carbon matrix obtained in step (2) was rinsed, dried and placed in a tubular furnace, and 4 g of dicyandiamide was added to the front end. The temperature was increased from room temperature to 400 ° C for 3 h at a heating rate of 10 ° C / min under an argon atmosphere, and then increased to 800 ° C for 1 h at a heating rate of 5 ° C / min. After natural cooling, a MOF-derived carbon nanotube / carbon matrix composite material with a tube diameter of 100 to 200 nm was obtained.
[0082] The MOF-derived carbon nanotube / carbon matrix composite material (denoted as CG-800) prepared in Example 2 was subjected to XRD analysis, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the original carbon felt and the MOF-derived carbon nanotube / carbon matrix composite material of this embodiment have similar diffraction peaks at 25.8°, which is the crystal plane (002) of graphite carbon, and show diffraction peaks of the (111) and (200) crystal planes of Co metal element at 44.2° and 51.3°.
[0083] Application Example 1
[0084] (1) A bismuth vanadate / tungsten trioxide semiconductor material film and a commercial silicon battery are stacked as a composite photoanode, and the MOF-derived carbon nanotube / carbon matrix composite material prepared in Example 1 is used as a cathode, and placed in a quartz reaction cell containing a Na2SO4 solution containing uranyl ions. The hybrid series photocatalytic fuel cell is connected to the cathode through an external circuit;
[0085] (2) The concentration of uranyl ions is 20 mg / L, the concentration of Na2SO4 is 0.1 mol / L, and the power consumption is 100 mW·cm -2 The simulated sunlight source is irradiated on the composite photoanode. The photoanode generates photogenerated charges, and the partially light-excited photovoltaic cell of the transmission film generates voltage to efficiently drive the photogenerated electrons to migrate to the cathode through the external circuit, and electrode reactions occur on the surface of the film electrode and the cathode respectively, and a loop is formed through the external circuit, so that self-driven photocatalytic removal of uranyl ions in water can be achieved.
[0086] In this application example, during the degradation of uranyl ions, the uranyl ion concentration was measured at 0, 5, 10, 15, 20, and 25 minutes. The results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that after 25 minutes, the removal efficiency of uranyl ions reaches 100%, which is higher than that of the original carbon substrate (removal rate is 25%).
[0087] Under this condition, the uranium removal experiment was repeated 30 times. The results are as follows: Fig.10 As shown. Fig.10It can be seen that the uranyl removal efficiency is good after 30 consecutive cycles, and the removal rate is kept above 97%, indicating that the system composed of the composite photoanode and the electrode material of the present invention has excellent stability.
[0088] Application Example 2
[0089] A bismuth vanadate / tungsten trioxide semiconductor material film and a commercial silicon battery were stacked as a composite photoanode, and the MOF-derived carbon nanotube / carbon matrix composite material prepared in Example 2 was used as a cathode. They were placed in a quartz reaction cell containing 0.1M Na2SO4 solution, and the hybrid series photocatalytic fuel cell was connected to the cathode through an external circuit.
[0090] In the process of decomposing water to produce hydrogen in this application example, the photoanode generates photogenerated charges, and the partially light-excited photovoltaic cell of the transmission film generates voltage to efficiently drive the photogenerated electrons to migrate to the cathode through the external circuit, and oxidation-reduction reactions occur on the surface of the film electrode and the cathode respectively, and a loop is formed through the external circuit, so that self-driven photoelectric catalytic decomposition of water to produce hydrogen can be realized. Under simulated sunlight, the hydrogen production rate reaches 45 μmol cm -2 h -1 .
[0091] In the process of cyclic testing of decomposing water to produce hydrogen, the hydrogen production efficiency did not show obvious attenuation after 10 cycles, showing good stability.
[0092] Application Example 3
[0093] The MOF-derived carbon nanotube / carbon matrix composite material prepared in Example 3 was used as a working electrode, a metal platinum sheet was used as a counter electrode, and an Ag / AgCl reference electrode was used as a reference electrode. The working electrode, the counter electrode, and the reference electrode were immersed in a 0.1 M NaSO4 solution to form a three-electrode system.
[0094] In this application example, in the electrochemical decomposition of water for oxygen evolution (1M KOH solution, platinum electrode as counter electrode), the MOF-derived carbon nanotube / carbon matrix composite material obtained in Example 3 was 10 mA / cm 2 The current density shows a lower potential, and the overpotential is only 0.3V. When used as an electrode of a supercapacitor (kraft paper as the medium, effective area 5cm 2 ) when tested, it can be 1mA / cm 2 Provides 601.9Fg at a current density of -1 The specific capacitance of the battery is 5 mA / cm 2 After 3000 charge and discharge cycles, 84% of the capacity was retained.
[0095] Comparative Application Example 1
[0096] The only difference from the application example is that the MOF-derived carbon nanotube / carbon matrix composite material of Example 1 is replaced with carbon felt as the cathode.
[0097] The uranyl ion concentration was measured at 0, 5, 10, 15, 20, and 25 minutes. Fig. 9 As shown. Fig.11 It can be seen that under the same conditions, uranyl is degraded by 25% after 25 minutes.
[0098] That is, the degradation efficiency of the carbon cathode using the MOF-derived carbon nanotube / carbon matrix composite material of Example 1 is 3.9 times that of the carbon felt used as the cathode.
[0099] Comparative Application Example 2
[0100] The only difference from Application Example 3 is that carbon felt is used as the working electrode instead of the MOF-derived carbon nanotube / carbon matrix composite material prepared in Example 3.
[0101] The three-electrode system composed of Example 3 and Comparative Application Example 2 was tested by cyclic voltammetry. The results are as follows Fig.11 As shown. Fig.11 It can be seen that the MOF-derived carbon nanotube / carbon matrix composite material of Example 3 has a higher current density at different voltages compared with the carbon felt, indicating that it has good electrocatalytic activity and conductivity.
[0102] The impedance test of the three-electrode system composed of Example 3 and Comparative Application Example 2 is carried out. The results are as follows Fig.12 As shown. Fig.12 It can be seen that under a bias voltage of 0.8 V, the MOF-derived carbon nanotube / carbon matrix composite material of Example 3 has a smaller semicircular diameter than the carbon felt, indicating good charge transfer efficiency.
[0103] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. Application of MOF-derived carbon nanotube / carbon matrix composite material as electrode material in photoelectrocatalytic system, characterized in that: When the electrode material is used to remove uranyl ions, the method of application comprises the following steps: placing the composite photoanode and the electrode material in wastewater containing uranyl ions, and connecting the electrode material to a hybrid series photocatalytic fuel cell through an external circuit to remove the uranyl ions; When the electrode material is used to decompose water to produce hydrogen, the application method comprises the following steps: After placing the composite photoanode and the electrode material in an electrolyte solution, the electrode material is connected to a hybrid series photocatalytic fuel cell through an external circuit to decompose water and produce hydrogen; When used to remove uranyl ions or decompose water to produce hydrogen, the composite photoanode is a superposition of a semiconductor material film and a commercial silicon battery; the semiconductor material film includes one of a titanium dioxide film, a tungsten trioxide film, a bismuth vanadate film, and a bismuth vanadate / tungsten trioxide heterojunction film; The method for preparing the MOF-derived carbon nanotube / carbon matrix composite material comprises the following steps: The carbon matrix, the cobalt salt solution and the dimethyl imidazole solution are mixed to generate a coordination reaction, and a MOF material is formed on the surface of the carbon matrix to obtain a MOF-modified carbon matrix; the carbon matrix is a carbon felt; Decomposing a carbon source containing N in an inert atmosphere to form a high-C and high-N atmosphere; Carbonizing and reorganizing the MOF-modified carbon matrix in the high-C and high-N atmosphere to obtain a MOF-derived carbon nanotube / carbon matrix composite material; The temperature of the carbonization and recombination is 600-800°C, and the time is 1-6 hours; the temperature of the decomposition reaction is 400-500°C, and the time is 1-4 hours.
2. The use according to claim 1, characterized in that: The MOF loading in the MOF-modified carbon matrix is 0.3-0.5 mg / cm 2 .
3. The use according to claim 1, characterized in that: The cobalt salt solution includes a cobalt sulfate solution or a cobalt nitrate solution.
4. The use according to claim 1, 2 or 3, characterized in that: The molar ratio of the cobalt salt in the cobalt salt solution to the dimethylimidazole in the dimethylimidazole solution is 1:4-10.
5. The use according to claim 1, characterized in that: The mass ratio of the MOF-modified carbon matrix to the N-containing carbon source is 1:0.4-1.
6. The use according to claim 1 or 5, characterized in that: The N-containing carbon source includes one or more of urea, dicyandiamide and melamine.
7. The use according to claim 1, characterized in that: The heating rate of heating to the temperature of the decomposition reaction and the heating rate of heating to the carbonization and recombination temperature are independently no higher than 10°C / min.
8. The use according to claim 1, characterized in that: The MOF-derived carbon nanotube / carbon matrix composite material comprises a carbon matrix and MOF-derived carbon nanotubes loaded on the carbon matrix; the MOF-derived carbon nanotubes contain elements C, N, O and Co, and have a tube diameter of 10-250 nm.
Citation Information
Patent Citations
Photovoltaic cell using catalyst-supporting carbon nanotube and method for producing the same
CN101106165A
Cobalt-nitrogen co-doped carbon nanotube modified graphene fiber as well as preparation and application thereof
CN112726193A